THE PERSONAL-RELATIONSHIPS PROBLEMS OF WOMEN WHO HAD ADDICTED HUSBAND: A Perspective to Their Rehabilitation - Parvaneh Mohammadkhani (Drug Control Headquarters, Research and Education Office, 2009)
Addiction can have adverse effects on morality in society and consequently because of dependency may destroy morality and cause crime, hostility and violence directly and indirectly. Addicted family and their first degree relatives suffer because of these addiction consequences and are victims. The study was based on a expost factor and cross sectional research method. It determines the personal-relationship problems of women with addicted husband by comparison with women having unaddicted husband. The subjects of the study consisted of 186 women (the mean age=36 and SD=9) whom their husband had received treatment for their addiction and came to receive professional services of outpatient addiction treatment centers at least once (from December 2007 to February 2008). These centers are located in different parts of Tehran. 173 women with unaddicted husband who were among the relatives, neighbors and friends of the first group were chosen as comparison group. A clinical interview for all subjects from both groups were conducted to confirm include and exclude research criteria. Data were gathered by: 1) Demographic Questionnaire 2) Personal and Relationship Profil(PRP,Struas etal,1999) Results showed the differences between two groups in all of Personal and Relationship Profile subscales except in Jealousy,And indicated that women with addicted husband had more symptoms in Antisocial Personality, Borderline Personality, Depression, Stress, violence Approval. They also reported a history of abuse and neglect. In relationship profiles they had more problems in Conflict, Communication Anger Management, and Relationship Commitments (particularly with their husbands) and Negative Attribution subscales. These differences display a higher level of problems in women who had addicted husband.So any rehabilitation program must consider all these problems and psychopotology